Coordination stability between the legs is reduced after anterior cruciate ligament reconstruction. (October 2018) - Armitano, Cortney N.; Morrison, Steven; Russell, Daniel M.
Abstract: Background: The study was designed to examine coordination differences in walking between individuals with an anterior cruciate ligament reconstruction compared with healthy matched controls. Predictions from the extended Haken, Kelso, and Bunz coupled oscillator model were tested in these populations. Methods: Seventeen persons with anterior cruciate ligament reconstruction and 17 matched controls participated in the study. Sagittal plane angular knee displacement was recorded using electrogoniometers over the lateral right and left knee joints while participants walked at five walking speeds overground. Coordination pattern and stability between the knees were quantified by mean and standard deviation of relative phase, respectively. Findings: Mean relative phase was not influenced by walking speed or group. For both groups, coordination stability was maximal when individual's walked at their preferred gait speed. However, the anterior cruciate ligament reconstruction group demonstrated reduced coordination stability compared with healthy controls across the five speeds. Multiple regression analyses found that people with anterior cruciate ligament reconstruction who deviated more from antiphase coordination had decreased coordination stability. Interpretation: Anterior cruciate ligament reconstruction results in decreased coordination stability, indicative of reduced coupling strength between the legs. This change in gait coordination, which has not previously been found in the literature, may contribute to the increased rate of re-injury and degeneration in individuals who have had this reconstructive surgery. Application of a motor control model enhances our understanding of the influence of an injury on coordination during gait. Highlights: Gait coordination after anterior cruciate ligament reconstruction was assessed. Coordination between the legs was most stable at the preferred walking speed. Anterior cruciate ligament reconstruction reduces coordination stability thru gait. Coupling strength between knees decreases after reconstructive surgery. Individual differences after knee ligament reconstruction influence coordination.